2005
DOI: 10.1001/archpedi.159.5.440
|View full text |Cite
|
Sign up to set email alerts
|

HIV/STD Risk Reduction Interventions for African American and Latino Adolescent Girls at an Adolescent Medicine Clinic

Abstract: Skill-based HIV/STD interventions can reduce sexual risk behaviors and STD rate among African American and Latino adolescent girls in clinic settings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
257
1

Year Published

2005
2005
2012
2012

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 227 publications
(265 citation statements)
references
References 41 publications
7
257
1
Order By: Relevance
“…The overall findings highlight the value of culturally grounded HIV prevention programs for Mexican American youth that are created in collaboration with community members and address ecological factors affecting adolescent sexual behaviors (Jemmott et al, 2005;Lesser, Koniak-Griffen, Gonzalez-Figueroa, Huang, & Cumberland, 2007;Pantin et al, 2004). Results are also consistent with the psychosocial and psycho-educational factors that are integral to successful progression through the three stages of the ARRM (Catania et al, 1990).…”
Section: Discussionsupporting
confidence: 62%
See 2 more Smart Citations
“…The overall findings highlight the value of culturally grounded HIV prevention programs for Mexican American youth that are created in collaboration with community members and address ecological factors affecting adolescent sexual behaviors (Jemmott et al, 2005;Lesser, Koniak-Griffen, Gonzalez-Figueroa, Huang, & Cumberland, 2007;Pantin et al, 2004). Results are also consistent with the psychosocial and psycho-educational factors that are integral to successful progression through the three stages of the ARRM (Catania et al, 1990).…”
Section: Discussionsupporting
confidence: 62%
“…That is, although participants might have perceived themselves to be at risk for HIV and developed a conscious commitment to preventing infection, they did not change their behavioral practices (e.g., employ sexual assertiveness skills) because they were not currently sexually active. These results coupled with the occurrence of group differences in condom use at the 2-month follow-up and not at immediate posttest, also support the need to evaluate intervention effects for longer periods of time (e.g., 12-month follow-up), as other prevention trials have observed delayed intervention effects (Jemmott et al, 2005;Lauby, Smith, Stark, Person, & Adams, 2000;Sales, Smith, Curran, & Kochevar, 2006). Longer follow-up periods also provide more opportunities for participants to implement safer sex practices with existing and new sexual partners (St. Lawrence, Wilson, Eldridge, Brasfield, & O'Bannon, 2001).…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…Consequently researchers should be aware of the selection bias [31] that may be operating in these types of studies, and intervention strategies designed to target the extremely hard-to-reach populations should be designed. Such strategies could include a more intensive approach such as the fullday sessions used by other researchers [32]. Despite the inherent selection bias in these types of studies, the examined population that is being followed still represents a high-risk population deserving of interventions and assessment.…”
Section: Discussionmentioning
confidence: 99%
“…31 However, a skills-based intervention implemented by African American educators in a mixed cohort with both African American and Latino adolescents was more successful than the didactic control, with no significant difference in impact on STI rates or sexual risk behavior between the two racial groups. 32 Several studies have attempted to adopt the above insights using digital or other media to develop economical interventions for adolescents with mixed results. One intervention for primarily African American young adolescents was implemented in the offices of private practice pediatricians.…”
Section: Adolescentsmentioning
confidence: 99%